FENOMENA POLITISASI BIROKRASI SELAMA PILKADA DI INDONESIA - Wisnu Yuda Pratama; Muh. Afif Baihaq; Asy'Ari Wais Alqorni (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The politicization of the bureaucracy which is a pathology in the body of the bureaucracy in Indonesia still thrives when general elections are held. ASN mobilization during regional elections, post-election post-election compensation, and removal of career positions for political reasons often have implications for the performance of bureaucratic substance which will decline due to complex reasons. The writing method uses a qualitative study approach with the desk research method. This study seeks to dig up data from various sources as secondary data in order to describe phenomena of bureaucratic politicization, rules governing ASN actions and the use of the merit system as a bureaucratic measure to maintain the neutrality principle of ASN in regional elections over the substance of the rules in force. The neutrality of ASN which has changed due to political intervention has led to a "buying and selling" of positions politically. The politicization that occurred caused ASN to find it easy to get the position compensation they wanted. The merit system that should be used by the bureaucracy should be used as the main requirement to prevent political intervention, especially before and after the elections. The merit system must be used as a way of classifying the state civil apparatus in order to produce competent human resources within the bureaucracy. But it's not enough there, the rules still view that the offense of prohibition against ASN actions that are not allowed to carry out political activities during the Pilkada only ends in principle as "principle". It is only this principle that causes the tendency of ASN not to be too subject to laws and regulations which causes the politicization of the bureaucracy in Indonesia to still occur.